Salvianolic acid A attenuates inflammation-mediated atherosclerosis by suppressing GRP78 secretion of endothelial cells. (23rd May 2023) - Fan, Xiaxia; Zhang, Lichao; La, Xiaoqin; Tian, Jinmiao; Israr, Ghani; Li, Aiping; Wu, Changxin; An, Yuxuan; Li, Songtao; Dong, Xiushan; Li, Zhuoyu
Abstract: Ethnopharmacological relevance: Salvianolic acid A (SAA) is the main active component of the classic anti-atherosclerotic drug Salvia miltiorrhiza Bunge . Inflammation-induced infiltration of monocyte/macrophages into the vascular wall is the initiating step in atherogenesis, and targeted blocking of this step may provide a promising avenue for the precise treatment of atherosclerosis. However, the effect of salvianolic acid A on macrophages is still unknown. Aim of the study: To evaluate the effect of SAA on macrophage infiltration and the underlying mechanism of SAA against atherosclerosis. Materials and methods: Vascular endothelial cells were stimulated with lipopolysaccharide (LPS) to simulate the inflammatory environment, and its effect on monocyte/macrophages was evaluated. Mass spectrometry was used to identify the proteins that play a key role and further validated them. LncRNA sequencing, western blot analysis, RNA immunoprecipitation, and RNA pulldown were used to elucidate the mechanism of SAA against atherosclerosis. Finally, ApoE −/− mice were fed a high-fat diet to creat an in vivo atherosclerosis model. Secretory GRP78 content, lipid levels, plaque area, macrophage infiltration, and degree of inflammation were assessed by standard assays after 16 weeks of intragastric administration of SAA or biweekly tail vein injections of GRP78 antibody. Results: After LPS stimulation, the increased secretion of GRP78 recruits circulating monocyte/macrophages and drives monocyte/macrophage adhesion and invasion into the vascular intima to promote atherosclerosis progression. Interestingly, SAA exerts anti-atherosclerosis effects by inhibiting the secretion of GRP78. Further mechanistic studies indicated that SAA upregulates the expression of lncRNA NR2F2-AS1, which reverses the abnormal localization of the KDEL receptor (KDELR) caused by inflammation. It promotes the homing of GRP78 from the Golgi apparatus to the endoplasmic reticulum rather than secreting outside the cell. Conclusion: SAA alleviates atherosclerosis by inhibiting GRP78 secretion via the lncRNA NR2F2-AS1-KDELR axis. The findings not only provide a new direction for the precise therapy of atherosclerosis based on secretory GRP78 but also elucidate the pharmacological mechanism of SAA against atherosclerosis, putting the foundation for further development and clinical application of SAA drugs. Graphical abstract: Increased GRP78 secretion of endothelial cells drives macrophage infiltration to promote atherogenesis. SAA upregulates the expression of lncRNA NR2F2-AS1, reverses the abnormal localization of KDELR, inhibits GRP78 secretion, and exerts anti-atherosclerosis effects in vivo . Image 1 Highlights: Intestinal-derived LPS stimulates endothelial cells to secrete more GRP78. GRP78-induced monocyte/macrophages infiltration into the vascular intima drives the progression of atherosclerosis. SAA exerts anti-atherosclerosis effects by inhibiting the secretion of GRP78, which was further verified in vivo. Interaction of lncRNA NR2F2-AS1 with KDELR mediates the blockade of GRP78 secretion by SAA.